RANCANG BANGUN SISTEM INFORMASI INVENTORI BAHAN BANGUNAN BERBASIS WEB PADA PB ADI JAYA - ulis, muhlis; SW, Sulistianto (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2023)
Errors in decision making often occur in every company, as well as in the PB Adi Jaya building material store. Manual transactions in recording incoming goods, outgoing goods, and other transactions that lack information in business processes are the cause of errors in decision making. The purpose of this research is to optimize the efficiency and effectiveness of the inventory management process and provide better accessibility to users in managing building material inventory. The development methodology used is object-oriented using the Rapid Application Depelovment (RAD) method to the testing stage using black-box testing. The tools used are UML (Unified Modelling Language), using the PHP programming language and MySQL database. The result of this research is an effective, efficient, user friendly Building Material Inventory Information System for PB Adi Jaya and is able to increase speed, accuracy, data availability, and avoid data redundancy, and produce an inventory application that has the features of recording incoming and outgoing goods, storing goods, and stock reports.